Prognostic implications and outcomes of cardiac arrest among contemporary patients with STEMI treated with PCI - Kumar, Anirudh (Resusc Plus, 2021)
BACKGROUND: Cardiac arrest (CA) complicating ST-elevation myocardial infarction (STEMI) is associated with a disproportionately higher risk of mortality. We described the contemporary presentation, management, and outcomes of CA patients in the era of primary percutaneous coronary intervention (PCI). METHODS: We reviewed 1,272 consecutive STEMI patients who underwent PCI between 1/1/2011-12/31/2016 and compared characteristics and outcomes between non-CA (N = 1,124) and CA patients (N = 148), defined per NCDR definitions as pulseless arrest requiring cardiopulmonary resuscitation and/or defibrillation within 24-hr of PCI. RESULTS: Male gender, cerebrovascular disease, chronic kidney disease, in-hospital STEMI, left main or left anterior descending culprit vessel, and initial TIMI 0 or 1 flow were independent predictors for CA. CA patients had longer door-to-balloon-time (106 [83,139] vs. 97 [74,121] minutes, p = 0.003) and greater incidence of cardiogenic shock (48.0% vs. 5.9%, p < 0.001), major bleeding (25.0% vs. 9.4%, p < 0.001), and 30-day mortality (16.2% vs. 4.1%, p < 0.001). Risk score for 30-day mortality based on presenting characteristics provided excellent prognostic accuracy (area under the curve = 0.902). However, over long-term follow-up of 4.5 ± 2.4 years among hospital survivors, CA did not portend any additional mortality risk (HR: 1.01, 95% CI: 0.56–1.82, p = 0.97). CONCLUSIONS: In a contemporary cohort of STEMI patients undergoing primary PCI, CA occurs in >10% of patients and is an important mechanism of mortality in patients with in-hospital STEMI. While CA is associated with adverse outcomes, it carries no additional risk of long-term mortality among survivors highlighting the need for strategies to improve the in-hospital care of STEMI patients with CA.